Comprehensive Maqasid Shariah Analysis of Qur'anic Verses on Adultery Prohibition and Its Social-Legal Implications - A Amir Firmansyah; Salma Ragil Hidayat; Dian Rizqi Pratiwi; Graiguer Abdelmounaim (UIN Kiai Haji Achmad Siddiq Jember, 2025)
In Islamic law, Muslims are prohibited from committing adultery because it causes moral damage to individuals and society. However, the rate of adultery continues to increase in Indonesia, which has the largest Muslim population. Previous studies on the adultery prohibition have mainly focused on the normative aspect. Therefore, an in-depth analysis using the maqasid shariah is needed to uncover more comprehensive implications. The focus is to explore the prohibition as a normative rule and a comprehensive safeguard for individuals, families, and society. This study employs a thematic exegesis method with a hermeneutic interpretation in library research, analyzing Surah al-Isra' 17:32, al-Nur 24:2, 24:30-31, al-Furqan 25:68-69, al-Nisa' 4:24, and al-Ahzab 33:59, along with the commentaries including Al-Tahrir wa al-Tanwir, Fi Zilalil Qur'an, Al-Munir, Tafsir al-Tabari, and Tafsir al-Qurtubi. The study analyzes Quranic verses prohibiting adultery in relation to the five maqasid shariah: hifz al-din, al-aql, al-nasl, al-nafs, and al-mal. This study reveals that the prohibition protects the maqasid shariah holistically to prevent damage to religion, intellect, offspring, life, and property. It also addresses supporting factors, such as dating, which can trigger unwanted pregnancy and abortion. Research findings reveal that adultery undermines social structures. The prohibition of adultery through hudud laws is a comprehensive Sharia strategy to safeguard societal well-being. This prohibition goes beyond normative prohibitions to safeguard human life universally. This research is expected to enrich the understanding of the objectives of Islamic law and encourage its contextual application in Indonesia.